Perancangan Fasilitas Kerja untuk Mereduksi Human Error - Harmein Nasution; Nazlina . (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2012)
Work equipments and environment which are not design ergonomically can cause physical exhaustion to the workers. As a result of that physical exhaustion, many defects in the production lines can happen due to human error and also cause musculoskeletal complaints. To overcome, those effects, we occupied methods for analyzing the workers posture based on the SNQ (Standard Nordic Questionnaire), plibel, QEC (Quick Exposure Check) and biomechanism. Moreover, we applied those methods for designing rolling machines and grip egrek ergono-mically, so that the defects on those production lines can be minimized.